The Influence of Servant Leadership on Employee Performance at PT. Saudara Buana Samudera Through Job Satisfaction - Wijaya, Elyzabeth (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
This research aims to examine the influence of the servant leadership model on employee performance at PT. Saudara Buana Samudera, with the mediator variable in the form of job satisfaction. This research uses a survey method by distributing questionnaires to employees PT. Saudara Buana Samudera. We selected the research sample using a purposive sampling technique and analyzed the data using the structural equation modeling (SEM) model. We expect the research findings to deepen our understanding of the impact of servant leadership on employee performance, and the role of job satisfaction as a mediator in this relationship. The management of PT. Saudara Buana Samudera aims to use the research results to develop more effective leadership and human resource management strategies.